1985
DOI: 10.4319/lo.1985.30.5.1000
|View full text |Cite
|
Sign up to set email alerts
|

Sinking characteristics of dinoflagellate cysts1

Abstract: This study reports the first direct measurements of the density and sinking rates of marine dinoflagellate cysts. Gyrodinium uncatenum, Gonyaulax tamarensis, and Scrippsiella trochoidea cysts had densities of 1.14, 1.24, and 1.32 g cm-3. No significant difference between cultured and natural cyst density was observed. Measured settling velocities ranged from 0.008 to 0.0 13 cm s-1 (6-l 1 m d-l). Settling rates calculated using the measured densities and reasonable assumptions about shape and orientation during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(62 citation statements)
references
References 21 publications
3
56
0
1
Order By: Relevance
“…may restrict them to shallow lakes and ponds or to benthic or littoral habitats. Even though the lorica densities reported in this study are high they are not unusual in structures and products produced by planktonic organisms -dinoflagellate cysts and copepod fecal pellets have densities comparable to the KerateZZa lorica (Komar et al 198 1;Anderson et al 1985).…”
Section: General Conclusionmentioning
confidence: 99%
“…may restrict them to shallow lakes and ponds or to benthic or littoral habitats. Even though the lorica densities reported in this study are high they are not unusual in structures and products produced by planktonic organisms -dinoflagellate cysts and copepod fecal pellets have densities comparable to the KerateZZa lorica (Komar et al 198 1;Anderson et al 1985).…”
Section: General Conclusionmentioning
confidence: 99%
“…Based on sediment-trap data in Onagawa Bay (Ishikawa & Taniguchi 1996), mass encystments of Scrippsiella trochoidea were found to occur in September and October when the bloom of the vegetative population was declining through depletion of cellular nutrient reserves. Encystment can be induced and enhanced by the depletion of nitrogen or phosphate or by the addition of sodium bicarbonate, respectively (Watanabe et al 1982 , Anderson & Lively 1985).…”
Section: Discussionmentioning
confidence: 99%
“…These suggestions seem to be confirmed by culture experiments carried out on oceanic species by Janofske and Karwath (2000) who showed that the obtained cysts were not hypnozygotes or resting cysts, being unconnected to a sexual phase. The estimated cyst sinking time (Anderson et al, 1985) should allow an oceanic specimen to encyst, fall to an optimal nutritionally richer water layer, and then excyst completing its life cycle in a few tens of meters. This would explain the high abundance of empty shells in the deep sea sediments as a by-product of dinoflagellates living in the upper waters.…”
Section: Discussionmentioning
confidence: 99%